ANALYSIS OF AIRBORNE MAGNETIC AND GRAVITY ANOMALIES OF PENINSULAR SHIELD, INDIA INTEGRATED WITH SEISMIC AND MAGNETOTELLURIC RESULTS AND GRAVITY ANOMALIES OF MADAGASCAR, SRI LANKA AND EAST ANTARCTICA - Mishra D.C.; Vijaya Kumar V.; Rajasekhar R.P. (My University, 2006)
Modelling of gravity and airborne magnetic data integrated with seismic studies suggest that the linear gravity and magnetic anomalies associated with Moyar Bhavani Shear Zone (MBSZ) and Palghat Cauvery Shear Zone (PCSZ) are caused by high density and high susceptibility rocks in upper crust which may represent mafic lower crustal rocks. This along with thick crust (44-45 km) under the Southern Granulite Terrain (SGT) indicates collision of Dharwar craton towards north and SGT towards south with N-S directed compression during 2.6-2.5 Ga. This collision may be related to contemporary collision northwards between Eastern Madagascar-Western Dharwar Craton (WDC) and Eastern Dharwar Craton (EDC). Arcuate shaped N and S-verging thrusts, MBSZ-Mettur Shear and PCSZ-Gangavalli Shear, respectively across Cauvery Shear zone system (CSZ) in SGT also suggest that the WDC, EDC and SGT might have collided almost simultaneously during 2.6-2.5 Ga due to NW-SE directed compressional forces with CSZ as central core complex in plate tectonics paradigm preserving rocks of oceanic affinity. Gravity anomalies of schist belts of WDC suggest marginal and intra arc basin setting. The gravity highs of EGFB along east coast of India and regional gravity low over East Antarctica are attributed to thrusted high-density lower crustal/upper mantle rocks at a depth of 5-6 km along W-verging thrust, which is supported by high seismic velocity and crustal thickening, respectively. It may represent a collision zone at about 1.0 Ga between India and East Antarctica. Paired gravity anomalies in the central part of Sri Lanka related to high density intrusives under western margin of Highland Complex and crustal thickening (40 km) along eastern margin of Highland Complex with several arc type magmatic rocks of about 1.0 Ga in Vijayan Complex towards the east may represent collision between them with W-verging thrust as in case of EGFB. The gravity high of Sri Lanka in the central part falls in line with that of EGFB, in case it is fitted in Gulf of Mannar and may represent the extension of this orogeny in Sri Lanka. © 2006 International Association for Gondwana Research.
Keywords: AIRBORNE MAGNETIC AND GRAVITY ANOMALIES; HIGHLAND COMPLEX; NAPIER COMPLEX; PROTEROZOIC COLLISION; SOUTHERN GRANULITE TERRAIN